Phosphorus mobilization induced by bio-based fertilizers from soils with varying phosphorus retention capacities - Ylivainio, Kari; Uusitalo, Risto; Nikama, Johanna; Bauerle, Andrea; Delgado, Antonio (Elsevier, 2026)
Phosphate fertilizer production relies on finite mineral resources. However, much of the phosphorus (P) taken up by crops eventually ends up in different waste streams. Ensuring P supply for agricultural sustainability requires a circular economy approach to producing bio-based fertilizers (BBFs) from these nutrient-rich side streams. This necessitates addressing not only the fertilizer value of BBFs but also the often-overlooked environmental impacts, which are surely affected not only by BBFs composition but also by soil properties. This study aimed to assess P losses promoted by BBFs, depending on their nature and the properties of soil to which they are applied, using a rain simulation after a 3-week incubation. To this end, 11 BBFs and triple superphosphate (TSP) were applied on soils originating from Finland (FI, pH 5.7), Germany (DE, pH 7.4), and Spain (ES, pH 8.1). The BBFs encompass a wide range of raw materials (plants, manure, animal by-products, sewage sludge) and production technologies (anaerobic digestion and composting, fermentation and distillation, various thermal treatments, and precipitation). The concentrations of dissolved reactive P (DRP) and molybdate-unreactive P (MU-P) in percolation water varied greatly depending on the soil properties and the P sources. Soil P tests that extract easily soluble P fractions predicted DRP concentrations in percolation water better than those extracting less soluble P fractions. The highest P concentration, especially DRP, was measured in the low P retention DE soil mixed with TSP. In acidic and calcareous soils, TSP, digested and composted pig slurry, and mineral/precipitate BBFs led to the greatest DRP mobilization. Organic BBFs containing tricalcium/hydroxyapatite and ash-based ones led to the least P mobilization in all soils. Granulation of BBFs effectively reduced P losses among BBFs with similar P speciation, while also offering improved handling and P utilization. Thus, compared with soluble mineral P fertilizers, BBFs offer a means to reduce P losses; however, minimizing P losses requires knowledge of both soil and BBF properties.
Keywords: soluble phosphorus; turbidity; phosphorus mobility; recycled fertilizers; precipitates; ash fertilizers